(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper offers the first comprehensive edition, following autopsy, of the graffiti on earthenware found at the Ibero-Roman site of Sigarra (now Els Prats de Rei in the province of Barcelona).